KARAKTERISTIK FISIKO-KIMIA KITOSAN DAN OLIGO KITOSAN KULIT UDANG (Litopenaeus vannamei) - Candra Candra; Findya Puspitasari (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2013)
This study aims to make chitosan and oligo-chitosan and studied its characteristics. The parameters tested in this study were moisture, ash, protein and fat content. Characteristics of chitosan depolimerasi process into oligo-chitosan were significantly lower levels of protein, ash, fat, white and degrees but there was an increase of water content, because due to the drying process was not optimal. Moisture, protein, ash content, white degree and viscosity of chitosan and oligochitosan were still below the quality standard due to less optimal deproteinization, demineralization, deacetylation and depolymerization. The higher of ash was decreasesolubility and viscosity of chitosan and oligo-chitosan.